Penetapan Pajak Penghasilan Pasal 21 Di Tengah Corona Virus Disease 19 Dalam Anggaran Pendapatan Dan Belanja Negara - Johanes Kristianto Pratama Limbers; Salmon Eliazer Marthen Nirahua; Heillen Martha Yosephine Tita (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: This research discusses the Covid 19 pandemic which has an impact on tax revenue collection so that it affects the state revenue and expenditure budget.Purposes of the Research: To find out and analyze state revenue through Article 21 income tax during the corona virus disease 19 period in accordance with the determination of the state revenue and expenditure budget..Methods of the Research: This study uses a normative juridical research type with a descriptive analysis type of research which in the problem approach uses a law, conceptual and case approach with primary, secondary and tertiary legal materials which are then used qualitative analysis techniques.Results of the Research: The Covid-19 pandemic has actually become a threat to all countries and all aspects, so it is not surprising that Article 21 income tax which is part of taxes in general and sources of state finances is also being threatened. As is known, in order to finance state expenditures, it must be stated in the state revenue and expenditure budget. Both the 2020, 2021 and 2022 state revenue and expenditure budgets continue to divert budgets for sectors impacted by Covid 19, one of which is the Article 21 income tax, which is then given incentives by the government for taxpayers. in accordance with the determination of the state revenue and expenditure budget due to Covid 19.